Temperature dependent moiré trapping of interlayer excitons in MoSe2-WSe2 heterostructures - Fateme Mahdikhanysarvejahany (Nature Portfolio, 2021)
Abstract MoSe2–WSe2 heterostructures host strongly bound interlayer excitons (IXs), which exhibit bright photoluminescence (PL) when the twist angle is near 0° or 60°. Over the past several years, there have been numerous reports on the optical response of these heterostructures but no unifying model to understand the dynamics of IXs and their temperature dependence. Here we perform a comprehensive study of the temperature, excitation power, and time-dependent PL of IXs. We observe a significant decrease in PL intensity above a transition temperature that we attribute to a transition from localized to delocalized IXs. Astoundingly, we find a simple inverse relationship between the IX PL energy and the transition temperature, which exhibits opposite power-dependent behaviors for near 0° and 60° samples. We conclude that this temperature dependence is a result of IX–IX exchange interactions, whose effect is suppressed by the moiré potential trapping IXs at low temperature.